Effect of incorporation of masonry residue on the properties of self-compacting concretes. (30th January 2019) - Silva, Yimmy Fernando; Lange, David A.; Delvasto, Silvio
Highlights: Self-compacting concrete was developed using residue of masonry (RM) as cement replacement material. The influence of RM on fresh properties of self-compacting concrete was studied. The effect of RM on mechanical properties of self-compacting concrete was investigated. RM improves the Compressive strength a long curing times in replacements lesser than 37.5%. Mechanical properties decline with increasing RM content in early curing days. Abstract: This paper presents the results of an experimental study about the effects of the incorporation of masonry residue (RM) on self-compacting concretes (SCCs). RM was composed of ground red clay bricks and cement Portland mortar. It was studied the influence of this RM addition on self-compactability properties of SCCs such as slump flow, V-funnel flow and L-box, and mechanical properties such as compressive, indirect tensile and flexure strength were determined. The Portland cement was partially replaced from 0% to 50% of RM in volume for the SCC blends. All the mixtures fulfilled the properties in fresh state, and specifically in the slump flow the mixtures presented a flow between 660 mm and 700 mm. As for the mechanical properties, the compressive strength was affected at different curing ages (7, 28 and 90 days) for all replacement levels showing much lower resistances if compared to the reference mixture (0% of RM); however, at longer days of curing (180 and 360 curing days) mixtures with 12.5%, 25% and 37.5% of RM showed similar or greater resistance.